2021
DOI: 10.1210/clinem/dgaa960
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside Enhances In Vitro Beta-adrenergic Brown Adipose Tissue Activity in Humans

Abstract: Context Elevating NAD+ levels systemically improves metabolic health, which can be accomplished via nicotinamide riboside (NR). Previously, it was demonstrated that NR supplementation in high fat diet (HFD)-fed mice decreased weight gain, normalized glucose metabolism and enhanced cold tolerance. Objective As brown adipose tissue (BAT) is a major source of thermogenesis, we hypothesize that NR stimulates BAT in mice and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The current investigation examined the impact of NRS on skeletal muscle metabolism in middle-aged male mice subjected to chronic high-fat feeding. We did not perform extensive analysis of the liver and we did not study the effect of the supplement on other organ systems such as brown adipose tissue (BAT)—a prominent thermogenic tissue implicated in the NRS-mediated increase in energy expenditure ( Crisol et al., 2018 ; Nascimento et al., 2021 ; Yamaguchi et al., 2019 ). Additionally, insulin sensitivity assessments were based on GTTs and ITTs rather than the hyperinsulinemic-euglycemic clamp technique, which is recognized as the gold standard measure of muscle insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…The current investigation examined the impact of NRS on skeletal muscle metabolism in middle-aged male mice subjected to chronic high-fat feeding. We did not perform extensive analysis of the liver and we did not study the effect of the supplement on other organ systems such as brown adipose tissue (BAT)—a prominent thermogenic tissue implicated in the NRS-mediated increase in energy expenditure ( Crisol et al., 2018 ; Nascimento et al., 2021 ; Yamaguchi et al., 2019 ). Additionally, insulin sensitivity assessments were based on GTTs and ITTs rather than the hyperinsulinemic-euglycemic clamp technique, which is recognized as the gold standard measure of muscle insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence to prove its therapeutic effects against aging and aging-related diseases is relatively limited. Several studies have reported that oral administration of NR could improve exercise performance, alter body composition, and enhance brown adipose tissue activity ( 30 32 ). In elderly people, 1 g of NR administration for 21 days was found to alter the mitochondrial-associated transcriptome in skeletal muscle and the circulating inflammatory cytokine profile; however, physiological parameters, such as body weight, blood pressure, lipid profile, and glucose metabolism, remained unaffected ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that reactive species overproduction can induce uncoupling that spares destructive oxidation of mitochondrial oxidative phosphorylation machinery. Nevertheless, in human subjects, NR had no impact on thermogenesis ( Nascimento et al, 2021 ), leaving the question open about how these findings can be translated to humans.…”
Section: Discussionmentioning
confidence: 99%
“…NAD + metabolism is linked to adipocyte differentiation (Luo et al, 2017;Ryu et al, 2018;Huang et al, 2020;Szanto and Bai, 2020;Szanto et al, 2021) Nicotinamide-riboside (NR) is an NAD + precursor that efficiently induces cellular NAD + levels and mitochondrial biogenesis (Canto et al, 2012). NR supplementation efficiently induced mitochondrial biogenesis in models of obesity (Canto et al, 2012;Jukarainen et al, 2016;Rappou et al, 2016;Jokinen et al, 2017;Asnani-Kishnani et al, 2019;Vannini et al, 2019;Nascimento et al, 2021), inflammatory diseases (Wu et al, 2022), Parkinson's (Brakedal et al, 2022), non-alcoholic fatty liver disease (Dall et al, 2021), and aging (Sun et al, 2021). The objective of this study was to assess the effects of NR on the induction of shift of differentiation of white adipocytes to beige adipocytes (beiging) in a human adipose tissue-derived mesenchymal stem cell (hADMSC) model.…”
Section: Introductionmentioning
confidence: 99%